The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fped.2019.00555
|View full text |Cite
|
Sign up to set email alerts
|

Markers of NETosis Do Not Predict Neonatal Early Onset Sepsis: A Pilot Study

Abstract: Introduction: Early-onset sepsis in neonates potentially results in substantial morbidity and mortality. A key player in sepsis a neutrophil extracellular traps (NETs) to limit dissemination of pathogens. Aim of this study was to evaluate markers of NET formation in umbilical cord blood as a predictor of neonatal sepsis.Methods: Prospective study including term and preterm neonates. Umbilical cord blood samples were obtained immediately after birth and following markers of inflammation and NET formation were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Therefore, our findings indicate that neonates may have a lower capacity to fight these bacteria. In contrast, Stiel et al [ 39 ] reported that NET markers (e.g., NE, MPO, and cell-free DNA) in umbilical cord blood do not appear to be a predictor of the onset of neonatal sepsis within 72 h postpartum. This is in contrast with newer experimental data from Colón et al, which showed that infant C57BL/6 mice subjected to sepsis or LPS-induced endotoxemia produced significantly higher levels of NETs than adult mice [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings indicate that neonates may have a lower capacity to fight these bacteria. In contrast, Stiel et al [ 39 ] reported that NET markers (e.g., NE, MPO, and cell-free DNA) in umbilical cord blood do not appear to be a predictor of the onset of neonatal sepsis within 72 h postpartum. This is in contrast with newer experimental data from Colón et al, which showed that infant C57BL/6 mice subjected to sepsis or LPS-induced endotoxemia produced significantly higher levels of NETs than adult mice [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings must be interpreted with caution, because of the low sample size included in the study. In a previous study, NET markers in umbilical cord blood drawn immediately after birth were unable to predict future EONS in neonates [ 17 ]. The main reason may be that prenatal NET formation is limited by the neonatal NET inhibitory factor (nNIF), which can be found in cord blood samples of neonates [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…All data were analyzed using SPSS Statistics 26 (IBM, Armonk, NY, USA) and GraphPad Prism 9 (GraphPad, San Diego, CA, USA). As this was a pilot study, power estimation was deduced from previous trials regarding sepsis in neonates [ 17 ]. Differences between groups were calculated using Mann–Whitney tests.…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, Stiel et al collected statistics of complete blood count, C-reactive protein (CRP), IL-6, levels of cell-free DNA (cfDNA), neutrophil elastase (NE) and myeloperoxidase (MPO) in umbilical cord blood to try to predict the early-onset sepsis. Unfortunately, the markers of NETosis they testified could not predict the happening of sepsis (149).…”
Section: Clinical Research Statusmentioning
confidence: 99%